GEFS+ Genetik Epilepsi Febril Nöbet Artı - Akça, Ünal (Canpolat, Temel Pediatrik Epilepsi, 2024)
Genetik Epilepsi Febril Nöbet artı (GEFS+), klasik febril nöbetler ile Dravet sendromu arasında değişen heterojen klinik fenotipler içeren bir ailevi epilepsi sendromudur. Aynı ailede en az biri febril olmak üzere aynı veya farklı GEFS+ fenotipinde nöbeti olan 2 veya daha fazla bireyin olduğu aileler GEFS+ ailesi olarak tanımlanmıştır. Sıklıkla otozomal dominant ve inkomplet penetrans ile kalıtım gösterir. Hem voltaj kapılı hem de ligand kapılı iyon kanallarını kodlayan genler, GEFS+ etiyolojisinde rol oynamaktadır. SCN1A, SCN1B, GABRG2, GABRD2, STX1B, HCN1, HCN2 gibi çeşitli mutasyonlar bildirilmiştir. Prognoz ve EEG bulguları klinik fenotipe göre değişkenlik göstermekle birlikte nadir görülen epileptik ensefalopatiler haricinde genel olarak kendini sınırlayan ve iyi prognozlu bir sendromdur. Genetic Epilepsy Febrile Seizure plus (GEFS+) is a familial epilepsy syndrome with heterogeneous clinical phenotypes, ranging from classic febrile seizures to Dravet syndrome. A family is defined as a GEFS+ family if two or more individuals in the same family have seizures with the same or different GEFS+ phenotypes, at least one of which is febrile. GEFS+ is frequently inherited as autosomal dominant with incomplete penetrance. Genes encoding both voltage-gated and ligand-gated ion channels have been implicated in the aetiology of GEFS+. Various mutations, including those in SCN1A, SCN1B, GABRG2, GABRD2, STX1B, HCN1 and HCN2, have been reported. Although the prognosis and EEG findings vary according to the clinical phenotype, it is generally a self-limiting syndrome with a good prognosis, with the exception of rare epileptic encephalopathies.